The Challenges of Midfoot Surgery - Vinall, Phil (MD Conference Express, 2014)
Failed midfoot repairs can occur as a result of anatomic, patient, mechanical, and technical factors. This article discusses failed reconstructions, misaligned midfoot reconstruction, and the management of missed midfoot injuries.